OPTIMALISASI TUMBUH KEMBANG ANAK DALAM MEMBANGUN PENDIDIKAN MERUPAKAN TANGGUNG JAWAB ORANG TUA - Rosita Carolina (JURNAL KELUARGA SEHAT SEJAHTERA, 2014)
ABSTRACT Child is an investment in the family, so parents should prepare education for children as early as possible. Education for children, can not be separated from how where parents prepare children's education. The parents' education will affect future development. The first year of a child's life span is very important and critical in terms of growth and development of physical, mental, and psychosocial, which runs so fast that the first years of success to a large extent determine the future of the child. Families can be important in the acculturation patterns for children's character. Habituation is accompanied by example and reinforced by planting the underlying values ​​which gradually establish a culture and develop a relationship with God Almighty. On the basis of assumption is that education in the family is not just teach knowledge in children, more than the family also inculcate the habit (habituation) about which one is better so that children become aware of what is right and wrong, are able to feel good values ​​and ordinary do it. Education in the family should involve not only the good aspects of knowledge, but also feel good, and good behavior. Education in the family emphasis on habit or custom which constantly practiced and carried out in the family who were trained by the parents. Education in the family serves to develop the potential of the base in order to be a good, good minded, and well behaved. Strengthen and build a multicultural children's behavior, increasing competitive student civilization in the association in the community should be developed. Kata Kunci : Pendidikan karakter, peran orang tua, anak usia dini.